An experiment study on the identification of noise sensitive individuals and the influence of noise sensitivity on perceived annoyance. (1st January 2022) - Di, Guoqing; Yao, Yao; Chen, Cong; Lin, Qinhao; Li, Zhengguang
Abstract: The perceived annoyance of noise has a great difference among individuals with different noise sensitivity. This paper proposed a method to identify noise sensitive individuals based on the experimental results of noise perceived annoyance and studied the influence of noise sensitivity on perceived annoyance. 14 pink noise samples with loudness level ( L N ) between 30 phon and 95 phon and 59 transformer noise samples with L N between 60 phon and 90 phon were selected. 337 subjects (undergraduate students) were recruited randomly. The noise sensitivity score ( NSS ) of each subject was obtained through the Weinstein's noise sensitivity scale. Using the scale of noise annoyance assessment (11-point numerical scale) specified by ISO 15666-2003, perceived annoyance experiments of noise were conducted in a soundproof room. The subjects were divided into several groups according to the NSS of each subject. According to the difference of perceived annoyance between different groups, a certain NSS was chosen as the threshold to identify highly and lowly noise sensitive individuals. Results showed that the threshold was 110, i.e., the NSS of each highly noise sensitive individual was larger than or equal to 110 and the NSS of each lowly noise sensitive individual was smaller than 110. The perceived annoyance of highly sensitive individuals caused by transformer noise was 1.4 larger than that of lowly sensitive individuals on average. Based on 21 acoustic factors and 1 non-acoustic factor (noise sensitivity), the model of perceived annoyance of transformer noise established by stepwise regression indicated that the weight of the influence of noise sensitivity on perceived annoyance was up to 26%. The results of this study can provide a basis for identifying noise sensitive individuals and determining the influence of noise sensitivity on perceived annoyance.